GAMBARAN DIRI ANDREA HIRATA DALAM NOVEL EDENSOR: KONSEP TRAVEL WRITING CARL THOMPSON - Arie Azhari Nasution (POETIKA, 2015)
This research is about to review the self-image in the novel by Andrea Hirata, Edensor, which tells the story of his travels around Europe and some African countries as a form of travel writing. To discover how Andrea Hirata write and illustrate the discovery of spaces as a form of a report from the places he visited and how he positioned himself as a traveler, used the theory of  travel writing Carl Thompson to identify novel Edensor from concept Reporting The World, Revealing The Self, and Representing The Other. As a  result, Andrea Hirata identified as a romantic traveler who tends to give a picture of himsel fas an autobiography and more to self-awareness (self-consciously) displayed in each trip made because the motivation to find himself. Moreover, he recognizes himself as inferior to the West because he comes from the East.Keywords: Andrea Hirata, Edensor, Travel Writing, Postcolonial Studies, Travel, Self-Image